STATE POLICY OF SOCIAL PROTECTION OF CHILDREN AS A SOCIAL SAFETY FACTOR: HISTORICAL EXPERIENCE OF EUROPEAN COUNTRIES FROM THE 17th to 21th CENTURIES. - Surgova, Svitlana; Faichuk, Olena (Public Administration and Regional Development, 2021)
The historical aspect of the development of state social policy of social protection of children in Europe from the 17th to 21th centuries is considered in the article. The purpose of the article is to highlight the peculiarities of the historical development of the state policy of social protection of children in European countries of the 17th to 21th centuries and learning from the experience of social protection of children in the context of Ukraine's European integration. The regulatory framework of the system of social protection of children in Ukraine has been studied. The statistic on different categories of children in need of social protection by the state is analyzed. The structure of the system of social protection of children in Ukraine is considered. The research methodology is based on the principle of priority of universal human values. As part of the tools of the proposed work the theoretical one is the analysis and generalization of scientific sources, educational and methodological publications on the theme and synthesis, as well as comparison and generalization of data. Based on the analysis of materials on the peculiarities of social protection in the UK, Germany, France, Sweden and Norway, it was determined that the social protection of children in Europe is characterized by assistance to them in providing conditions for the realization of their rights and freedoms. Equally important is the setting up of various charitable institutions, schools, penal colonies that help children change, as well as the emergence of social services that protect the rights and interests of children. The authors suggest that in the course of the studying the history of the issue of state policy of children’s social protection, there is an opportunity for analogies, the implementation of already proven steps on the path of democratization of national social protection policy. The researchers see the prospects for further research in the study of global innovative forms of social protection and support for at-risk children.